ASASSN-14dq: a fast-declining Type II-P supernova in a low-luminosity host galaxy. Issue 2 (23rd July 2018) - Singh, Avinash; Srivastav, S; Kumar, Brajesh; Anupama, G C; Sahu, D K
Abstract: Optical broadband ( UBVRI ) photometric and low-resolution spectroscopic observations of the Type II-P supernova (SN) ASASSN-14dq are presented. ASASSN-14dq exploded in a low-luminosity/metallicity host galaxy UGC 11860, the signatures of which are present as weak iron lines in the photospheric phase spectra. The SN has a plateau duration of ${\sim}$ 90 d, with a plateau decline rate of 1.38 $\rm mag\ (100 \, d)^{-1}$ in the V -band, which is higher than most Type II-P SNe. ASASSN-14dq is a luminous Type II-P SN with a peak V -band absolute magnitude of –17.7 $\, ± \, $ 0.2 mag. The light curve of ASASSN-14dq indicates it to be a fast-declining Type II-P SN, making it a transitional event between Type II-P and II-L SNe. The empirical relation linking the steepness parameter and $\rm ^{56}Ni$ mass for Type II SNe was rebuilt with the help of well-sampled light curves from the literature. The estimated $\rm ^{56}Ni$ mass of ${\sim}$ 0.029 M⊙ for ASASSN-14dq is slightly lower for a luminous Type II-P SN. Using analytical light curve modelling, a progenitor radius of $\rm \sim\!3.6× 10^{13}$ cm, an ejecta mass of $\rm \sim\!10\ M_{\odot }$, and total energy of $\rm \sim\!1.8× 10^{51}$ erg were estimated for this event. The photospheric velocity evolution of ASASSN-14dq resembles that of a Type II-P SN, but the Balmer features (H α and H β) show relatively slow velocity evolution. The high-velocity H α feature in the plateau phase, the asymmetric H α emission line profile in the nebular phase, and the inferred outburst parameters indicate an interaction of the SN ejecta with the circumstellar material.